Studi Komparasi Penerapan Kelas Homogen dan Heterogen Terhadap Tingkat Motivasi Belajar Siswa - Ibermarza; Susilo Hidayah; Nurhafid Ishari (Bidayatuna, 2023)
The study of the phenomenon of Indonesian educational institutions, particularly that at Madrasah Aliyah Nurul Islam Bades Pasirian Lumajang in East Java, discovered a number of phenomena, including the use of homogeneous and heterogeneous classes based on majors and gender, low learning motivation from male homogeneous students, and student learning activity dominated by female students. This study aims to ascertain how students behave in class before to, during, and after learning activities. This homogeneous class is typically used in education under the direction of the ministry of religion to place restrictions on relationships between male and female pupils in accordance with Islamic law.  The paucity of classrooms that can be used for instruction and the small class size are two additional factors that are taken into account when applying it to heterogeneous classes. As can be seen from the aforementioned circumstances, scholars are interested in examining this phenomena because classroom managemen.